Multiculturalismo, Lucha por la Tierra y Violencia: la Organización Nacional Indígena de Colombia (1975-1998) - Uribe, Mauricio Alejandro Diaz (2019)
The objective of the thesis is to analyze the changes and tensions in the forms, speeches, demands and claims of the modern Colombian Indigenous Movement (MIC), through the analysis of the official documents of its most representative national organization: National Indigenous Organization of Colombia (ONIC). Besides, it focuses on the analytical review of various texts and speeches by the most recognized indigenous leaders of the movement. Since the emergence in the mid-1970s, and after the recognition of Colombia as a multiethnic and multicultural social state of law in the 1990s, the MIC was configured as a historical process around representations and imaginaries in relation to the "indigenous problem". The research problematizes and discusses historical struggles and claims, as well as the trajectories and narratives of indigenous organizations and their representatives. From the historical context that constitutes modernity-colonialism, the emergence and re-signification of the discourses on autonomy, territoriality and ethnic affirmation, it is in permanent tension between the modern state, ethnic identity and neoliberal multiculturalism. In the Colombian case, this tension is manifested in a social context of conflict and widespread violence. The territories of indigenous communities coexist with war between armed actors and the threatening presence of multinational companies interested in environmental goods and mineral resources. In this situation, the indigenous leaders, especially the ONIC, try to reconfigure their cultural practices based on their worldviews and their own development plans. Thus, they seek to maintain political unity in the cultural diversity, in the complex network actors and interethnic relations, adapting or disputing their incorporation into the dilemmas of the multicultural nation-state of the late twentieth century.